HUBUNGAN PERSEPSI DENGAN KESIAPSIAGAAN BENCANA PADA TENAGA KESEHATAN - I Made Dwie Pradnya Susila; Made Adi Wahyu Udaksana; Nur A’ini (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2020)
Background Indonesia is a country which is frequently to natural disasters, geographically locatedbetween two continents and the plate of fire. Badung Regency is the main entrance of tourists toBali so that the population movement in Badung Regency is very high. Badung Regency isrecorded as the highest contributor to disasters in Bali Province so disaster preparedness isneeded to reduce casualties and material losses. Objectives This study aims to determine therelationship of perception with disaster preparedness in village ambulance health workers.Method Cross sectional survey was conducted on 49 village ambulance health workers who wereselected in total sampling in the working area of Petang and Abiansemal Districts. Data collectionwas conducted in May 2019 using a questionnaire. Data analysis was performed univariate,bivariate with chi square and multivariate with binary logistic regression. Results The resultsshowed that only 42.9% of health workers had high levels of disaster preparedness. Perceivedbenefits related to disaster preparedness (AOR = 16.1; 95% CI: 1.83-141.35). Conclusion Theperception of benefits is related to disaster preparedness.